Utility of Back-Off Sets: An Overview. Issue 5 (11th October 2021) - Rodriguez, Juan; Hanney, William J.; Kolber, Morey J.; Cheatham, Scott
ABSTRACT: Back-off sets or down sets are a training paradigm that use an initial heavy loaded set followed by a subsequent rest period and a planned load reduction. Back-off sets are a way to maintain or increase training volume through a load reduction for subsequent sets. By reducing load, a desired number of repetitions can be achieved as opposed to a reduction in volume that would occur if a consistent load was maintained. Back-off sets have been shown to allow completion of a greater training volume which may be in part due to a potentiation effect. The use of back-off sets help to reduce the necessary length of interset rest periods. Back-off set utility may be influenced by factors including but not limited to training goals, training age, exercise type, protocol individualization, loading strategy, load-reduction strategy, and autoregulation. This discussion aims to provide an overview of the integration of back-off sets within resistance training programs by examining previous research and providing a synopsis of the variables that impact the efficacy of this strategy.